A GLP-1 Analog Liraglutide Reduces Intimal Hyperplasia After Coronary Stent Implantation via Regulation of Glycemic Variability and NLRP3 Inflammasome/IL-10 Signaling in Diabetic Swine - Xia, Jinggang; Li, Qinxue; Liu, Yayun; Ren, Quanxin; Gao, Jinhuan; Tian, Yi; Li, Jubo; Zhang, Baojie; Sun, Haichen; Liu, Shuang (Frontiers in Pharmacology, 2020)
Objective: This study aimed to explore whether treatment with the glucagon-like peptide-1 (GLP-1) analogue liraglutide reduces intimal hyperplasia after coronary stent implantation via regulation of glycemic variability, the NLRP3 inflammasome and IL-10 in diabetic swine. Methods: Fifteen pigs were divided into a diabetes mellitus (DM) group (n=6), a DM + liraglutide treatment group (L group) (n=6) and a sham group (n=3). A total of 24 everolimus-eluting stents were implanted in the left anterior descending and right coro¬nary arteries at 3 weeks. A novel continuous glucose monitoring system (GMS) was used for 2 weeks. The means and standard deviations (SDs) were measured and calculated by the GMS. At 22 weeks, the lumen area (LA), neointimal thickness (NIT), neointimal area (NIA) and percent area stenosis (%AS) were analyzed by optical coherence tomography. Plasma tumor necrosis factor-α, interleukin-6 and interleukin-10 were assayed by ELISA. The intima protein expression levels of NLRP3, interleukin-1β, interleukin-18 and interleukin-10 were examined using Western blot analysis. Histology was used to evaluate the healing response. In an in vitro study, THP-1 cells were divided into control, high glucose (HG), HG + liraglutide and HG + liraglutide + Exe(9–39) (a GLP-1 receptor inhibitor) groups. Results: The L group had a lower SD, NIT, NIA, and %AS; a larger LA; reduced inflammation and injury scores; lower expression levels of tumor necrosis factor-α, interleukin-6, NLRP3, interleukin-1β, and interleukin-18; and higher expression of interleukin-10 compared with those of the DM group (p < 0.05). In the in vitro study, similar results were obtained in the HG + liraglutide group, and Exe(9–39) abolished the effect of liraglutide (p < 0.05). Conclusions: Liraglutide treatment reduces intimal hyperplasia after stent implantation via regulation of glycemic variability, the NLRP3 inflammasome and IL-10 in diabetic pigs in a GLP-1 receptor-dependent manner. Reducing the inflammation induced by glycemic variability may be one of the cardioprotective mechanisms of liraglutide.